Zło i grzech w nauczaniu Sulpicjusza Sewera - Pochwat, Józef (Vox Patrum, 2014)
Sulpicius Severus (c. 360-420) was aware of the enormity of evil that people commit. He kept reminding, that the source of this situation is the sin of the first couple, Adam and Eve. A human being took side of Satan rather than God, and consequently developed all kinds of sins of disorder in a delicate field of human sexuality, various vices, murders and wars. Everyone commits sins, no matter who he is and what he does in life. Sulpicius Severus emphasized the truth that sin means disaster, loss of the most important values of freedom and happiness in God. An important feature in the teaching of Sulpicius Severus is his approach to the pagans and heretics. Both of them are treated by him as those who are under the influence of Satan; pagans – because by worshiping idols they venerate demons, and heretics – because by preaching false doctrines they submit to the spirit of lies, that is the spirit of Satan.